2014
DOI: 10.1080/02691728.2014.922640
|View full text |Cite
|
Sign up to set email alerts
|

The Social License: Empowering Communities and a Better Way Forward

Abstract: The term social license is generally understood as an intangible representation of ongoing approval or acceptance of a project by affected communities, which can be withdrawn at any time, distinct from a legal or regulatory license granted by a government. This paper looks at the concept through the lens of the extractive sector in the developing world and explores the history of violations of land and human rights of indigenous and rural communities living around these resources. While corporate actors often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…Morrison, 2014;Syn, 2014), have shown that strategic interventions aimed at managing these risks in projects could be facilitated by greater understanding of the structure and dynamics of stakeholder networks. They argue that not all stakeholders are equally important and strategic interventions should be aimed at the stakeholders with higher influence.…”
mentioning
confidence: 99%
“…Morrison, 2014;Syn, 2014), have shown that strategic interventions aimed at managing these risks in projects could be facilitated by greater understanding of the structure and dynamics of stakeholder networks. They argue that not all stakeholders are equally important and strategic interventions should be aimed at the stakeholders with higher influence.…”
mentioning
confidence: 99%
“…The first recorded reference to SLO comes from a 1996 Paper Industry Manufacturing Association Magazine article [25], which proposed that the paper industry needed to maintain environmental standards beyond that set by government in order to obtain an SLO from the public for their operations. Nevertheless, many articles credit Jim Cooney, a Canadian mine executive for coining the term in relation to the need of the mining industry to develop better relations with communities so as to be able to reduce opposition to mining even when the company had met its legal requirements [2,5,6,11,13,24,[26][27]. The term was simultaneously being applied to mining companies in Australia, where the concept was picked up by the Western Australian Technology & Industry Advisory Council, in a report on Western Australia's Minerals and Energy Expertise [28]; as well as in reference to the operation and expansion of multinational companies in Latin America and the pressures they faced in being "good environmental actors" [29].…”
Section: The Concept Of Social License To Operatementioning
confidence: 99%
“…While this may be the case, the reality of SLO lies in the recognition that the need for a SLO did not come from the "goodness of the corporate heart", but instead from the actual or potential objection or rejection of business projects and products by communities [2] (p. 318). The adoption of SLO therefore provides companies with the opportunity to not only prevent rejection by communities, and their potentially significant economic and reputational costs, but also to claim compliance or legitimacy without the approval of governments or legal bodies that enforce regulations [2,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations